Togo : Fifth Review under the Extended Credit Facility Arrangement-Press Release; Staff Report and Statement by the Executive Director for Togo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Togo's Fifth Review Under the Extended Credit Facility (ECF) Arrangement. The report highlights that the economic recovery seems to be taking hold. Inflation stood at 0.6 percent at end-July 2019. Given high debt levels, revenue mobilization efforts and spending prioritization should continue, while addressing the persistent underperformance on social spending to enhance economic inclusiveness and to reduce poverty. It is important to address the weaknesses in the two public banks transparently. A successful privatization of these two banks would safeguard financial stability and minimize costs to the State budget. Broader financial sector developments should also be monitored, and corrective actions should be taken as needed, including in terms of the high nonperforming loans. Structural reforms are progressing on tax policy, revenue administration, and public expenditure management. Significant progress has also been made in the improvement of the business environment, which is expected to boost domestic and foreign private investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet